Análisis del valor añadido a los procesos y procedimientos de los laboratorios de la ESPAM “MFL” - Basurto Vera, Kenia Yadira (2021)
The purpose of this degree work was to apply the analysis of the added value to the processes and procedures of the laboratories of the Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López”, with the aim of identifying the degree of relevance of the same. To comply with the research, scientific methods such as inductive, analytical and descriptive were used, applying techniques such as interviews, direct observation and experimentation, aimed at career directors and personnel in charge of laboratories, which contributed to the information gathering and identifying the current status of the activities carried out in the studied processes, from this analysis we proceeded to capture the graphic representation of the processes and procedures that originate in the general chemistry, environmental chemistry, biology laboratories molecular and plant biotechnology. Likewise, the added value analysis tool was applied, which allowed the assessment of the processes and procedures carried out, with which it was identified that there are activities that do not generate value in the processes of Third Level Degree Thesis and Research project , input that served to design improvement plans that contributed to efficiency and effectiveness. Given all the action of this research, it was found that it is essential to know and prioritize the problems found within the processes and procedures in search of the optimal use of the resources that intervene in them.